2010
DOI: 10.1163/156853710x531203
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Culture in Affective Empathy: Cultural and Bicultural Differences

Abstract: Empathy is essential for healthy relationships and overall well-being. Affective empathy is the emotional response to others' distress and can take two forms: personal distress or empathic concern. In Western cultures, high empathic concern and low personal distress have been implicated in increased prosocial behaviour (e.g., Eisenberg et al., 1989) and better emotion management and peer relations (e.g., Eisenberg and Fabes, 1998). Various factors have been examined with respect to affective empathy, but the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 39 publications
7
61
5
1
Order By: Relevance
“…There are circumstances that negatively influence empathy: levels of anxiety, claustrophobia, obesity, depression and stress [47]- [49]. In summary, the variability of observed empathy levels in this study, related to gender, cannot be explained.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…There are circumstances that negatively influence empathy: levels of anxiety, claustrophobia, obesity, depression and stress [47]- [49]. In summary, the variability of observed empathy levels in this study, related to gender, cannot be explained.…”
Section: Discussioncontrasting
confidence: 58%
“…On the other hand, other authors proposed that empathy has an impact in the emotional health and in the social field throughout culture [4] [43]- [46], besides it is correlated with the pro-social behavior and altruism and also inhibits the unsocial and aggressive behavior [47] [48]. There are circumstances that negatively influence empathy: levels of anxiety, claustrophobia, obesity, depression and stress [47]- [49].…”
Section: Discussionmentioning
confidence: 99%
“…These researchers concluded that living in a collectivist society accounts for a higher concern for others because these cultures firmly believe that one's well-being depends on the well-being of others. In contrast, Cassels, Chan, and Chung (2010) found higher trait empathy in culturally individualist participants compared to their Cross-Cultural Approach to Empathy culturally collectivist peers. They attributed lower level of empathy in Eastern participants to high degree of their emotional dependency on other members of the same culture.…”
Section: Purpose Of Studycontrasting
confidence: 61%
“…Sample 2 included 203 Iranians (38 males; M = 22.68, SD = 3.90; age-range = 17-30) living either in Iran or outside the country who voluntarily consented for participation. Forty-three participants living outside Iran were excluded from analysis due to exposure to diverse cultures that might affect trait empathy (Cassels et al, 2010 Table 1.…”
Section: Participantsmentioning
confidence: 99%
“…On the one hand, it has been proved that cultural differences have an important influence on empathy. Eastern cultures and western cultures are distinct in empathic processing patterns (Adams Jr et al, 2010;Cassels et al, 2010;Birkett, 2014). On the other hand, participants in this study were well educated, so these results may limit their generalizability to other populations.…”
Section: Limitationsmentioning
confidence: 80%